Comparison between Manual Blood Culture and Automated Blood Culture System in Cardiology Institute - Syed Khizar Abbas; Syed Jawad Hussain Shah (Medical Journal of South Punjab, 2020)
Objective: In this study we compared the two techniques used for detection of microorganisms. Study Design: Retrospective cross-sectional. Place and Duration: study was conducted at Choudhary Pervaiz Ellahi Institute of Cardiology, Multan from 2018 to 2019. Methodology: Blood culture is gold standard for the detection of bacteremia. Two types of techniques are used for blood cultures which are the manual blood culture system (conventional) and the automated blood culture system (modern). We conducted 214 blood culture tests on manual blood culture system and 339 on automated blood culture system ( bact/alert). Results: The percentage of positive yield was 10.3 with manual blood culture system and percentage of positive yield was 15.3 with bact/alert which is significantly higher. Conclusion: This finding will contribute to reduction in mortality of patients with sepsis in our hospital and we recommend use of automated blood culture system over manual blood culture system at tertiary care hospitals.